2018
DOI: 10.2337/db18-2147-p
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extra Virgin Olive Oil Polyphenols on Pancreatic Beta-Cell Function and Survival

Abstract: Extra virgin olive oil (EVOO) is one of the major components of the Mediterranean diet and is appreciated worldwide because of its nutritional benefits in metabolic diseases, including type 2 diabetes. In addition to high levels of fatty acids, EVOO contains significant amounts of micronutrients such as polyphenolic compounds that may positively influence the metabolic status. In this study, we have evaluated the effects of such EVOO polyphenolic compounds on beta-cell function and survival. INS-1E cells were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These results were in agreement with Natalicchio et al (2018) [29], who confirmed the positive effects of the main polyphenols contained in extra virgin olive oil on beta-cell function and survival suggesting that extra virgin enriched with these compounds might improve insulin secretion and promoted glycaemic control in type 2 diabetic patients.…”
Section: Blood Analysissupporting
confidence: 92%
“…These results were in agreement with Natalicchio et al (2018) [29], who confirmed the positive effects of the main polyphenols contained in extra virgin olive oil on beta-cell function and survival suggesting that extra virgin enriched with these compounds might improve insulin secretion and promoted glycaemic control in type 2 diabetic patients.…”
Section: Blood Analysissupporting
confidence: 92%
“…Develop in vitro and in vivo experimental models to discover new beneficial effects of virgin olive oil extract by means of emerging technologies [34].…”
Section: Figurementioning
confidence: 99%